Ross Errilly Franciscan Friary, cloister, capital - O'Donovan, Danielle (My University, 2008)
Cloister capital, moulding from the top down comprises: abacus, ogee bell, chamfered fillet as necking roll.
Cloister
Keywords: chamfered fillet; Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Franciscan; Cloisters (Architecture); Gothic capitals (Architecture); Late Medieval; moldings, ogee; bell capitals